2010
DOI: 10.1080/02701367.2010.10599708
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Prolonged Altitude Expedition on Glucose Tolerance and Abdominal Fatness

Abstract: In the present study, we investigated the effect of a long-term mountain expedition on glucose tolerance and insulin action. Twelve registered mountaineers ages 31 years (SD = 1.1) participated in a 25-day expedition at a 2,200-3,800-m altitude with an average duration of 8 hr per day. Arterial oxygen saturation (SaO2) was substantially reduced during hiking. Glucose tolerance and insulin responses were measured prior to and twice during the expedition period. Maximal oxygen consumption increased from 43.0 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Manipulating food intake resulted in a weight change of between -1.0 and -0.6 kg, or up to -1.8 kg when combined with heavy military exercise (ET: 5 to 21 days) (Greenleaf et al, 1978; Schena et al, 1992; Hoyt et al, 1994). One study found no reduction in body weight (Chen et al, 2010; Chia et al, 2013). Reductions in FFM were reported to range from -3.1 to -0.2 kg whereas increases in FFM ranged from 0.7 to 1.6 kg (Schena et al, 1992; Gunga et al, 2003; Chia et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Manipulating food intake resulted in a weight change of between -1.0 and -0.6 kg, or up to -1.8 kg when combined with heavy military exercise (ET: 5 to 21 days) (Greenleaf et al, 1978; Schena et al, 1992; Hoyt et al, 1994). One study found no reduction in body weight (Chen et al, 2010; Chia et al, 2013). Reductions in FFM were reported to range from -3.1 to -0.2 kg whereas increases in FFM ranged from 0.7 to 1.6 kg (Schena et al, 1992; Gunga et al, 2003; Chia et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…One way to avoid this shortcoming would be to train an individual under normoxic condition but to recover under an extended period of moderate hypoxia. Such training method is effective to improve the whole-body glucose tolerance for lean individuals (Chen et al, 2010). Yet, it is unknown whether such a training method produces greater metabolic benefits for genetically obese animals than exercise training alone.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, insulin-mediated glucose uptake is inversely correlated with body fat mass [26][27] . In a previous study, hypoxic exposure (altitude 2,200-4,000 m) combined with aerobic exercise decreased body weight and fat mass [28][29][30] . Therefore, it could be used as a therapy for obesity with glucose control disorders.…”
Section: Effects Of Hypoxic Exposure On Glycemic Controlmentioning
confidence: 99%